2016
DOI: 10.2175/106143016x14504669768372
|View full text |Cite
|
Sign up to set email alerts
|

Co‐adsorption of Trichloroethylene and Arsenate by Iron‐Impregnated Granular Activated Carbon

Abstract: Co-adsorption of trichloroethylene (TCE) and arsenate [As(V)] was investigated using modified granular activated carbons (GAC): untreated, sodium hypochlorite-treated (NaClO-GAC), and NaClO with iron-treated GAC (NaClO/Fe-GAC). Batch experiments of single- [TCE or As(V)] and binary- [TCE and As(V)] components solutions are evaluated through Langmuir and Freundlich isotherm models and adsorption kinetic tests. In the single-component system, the adsorption capacity of As(V) was increased by the NaClO-GAC and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, the absorption capacity of toluene on both types of activated carbon and in all the tested conditions was higher than the absorption capacity of benzene (27). Lilo-Roudnas et al conducted a study to investigate the effects of competitive adsorption of benzene-toluene composition with a concentration of 200 ppm on 8 different samples of activated carbon (26). They reached similar results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the absorption capacity of toluene on both types of activated carbon and in all the tested conditions was higher than the absorption capacity of benzene (27). Lilo-Roudnas et al conducted a study to investigate the effects of competitive adsorption of benzene-toluene composition with a concentration of 200 ppm on 8 different samples of activated carbon (26). They reached similar results.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, with increase in the absorption bed depth, the absorption capacity of zeolite increased; however, with increase in air flow rate and inlet concentration, the absorption capacity decreased. In another study, the researchers investigated benzene absorption on two types of activated carbon; the first type was prepared from the wood composites cutting dust and the second type was a commercially supplied activated carbon prepared from coconut shell (26). Asilian et al reported that in the sampling of benzene as a VOC in ambient air by clinoptilolite zeolite, the mesh number of 80/60 compared to the mesh number of 60/40 has longer breakthrough time (27).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches for removal, degradation and detection of TCE have commonly included activated carbon [15,16,17,18,19,20,21,22,23] as a host and adsorbent. Even though activated carbon and naturally sourced materials such as pine needle biochar [24,25] have orders of magnitude advantages in cost, the use of two-dimensional carbon based materials (graphene nanosheets, graphene oxides and various carbon nanotubes (CNTs) with different chiralities) offers specificity in adsorption and remediation with relatively lower % loading in membranes and composites.…”
Section: Introductionmentioning
confidence: 99%